2-Terminal CIGS-perovskite tandem cells: A layer by layer exploration. (1st September 2020) - Jacobsson, T. Jesper; Hultqvist, Adam; Svanström, Sebastian; Riekehr, Lars; Cappel, Ute B.; Unger, Eva; Rensmo, Håkan; Johansson, Erik M.J.; Edoff, Marika; Boschloo, Gerrit
Graphical abstract: Stack sequence of a functional 2-terminal CIGS-perovskite tandem cell. Highlights: We demonstrate a functional 2-terminal CIGS-perovskite tandem cell. The 2-terminal CIGS-perovskite tandem cell is more efficient than the individual sub-cells. An account of insights, pitfalls, and suggestions gained for every layer in the stack is provided. The device data for every cell made in the project is disclosed. Abstract: This paper focuses on the development of 2-terminal CIGS-perovskite tandem solar cells by exploring a range of stack sequences and synthetic procedures for depositing the associated layers. In the end, we converged at a stack sequence composed of SLG/Mo/CIGS/CdS/i-ZnO/ZnO:Al/NiO/PTAA/Perovskite/LiF/PCBM/SnO2 /ITO. With this architecture, we reached performances only about 1% lower than the corresponding 4-terminal tandem cells, thus demonstrating functional interconnects between the two sub-cells while grown monolithically on top of each other. We go through the stack, layer-by-layer, discussing their deposition and the results, from which we can conclude what works, what does not work, and what potentially could work after additional modifications. The challenges for a successful 2-terminal tandem device include: how to deal with, or decrease, the surface roughness of the CIGS-stack, how to obtain uniform coverage of the layers between the CIGS and the perovskite while also obtaining a benign interface chemistry, and how to tune the band gaps of both the CIGS and the perovskite to obtain good optical matching. The investigation was based on CIGS with a power conversion efficiency around 14%, and perovskites with an efficiency around 12%, resulting in 2-terminal tandem cells with efficiencies of 15–16%. The results indicate that by using higher performing CIGS and perovskite sub-cells, it should be possible to manufacture highly efficient 2-terminal CIGS-perovskite tandem devices by using the protocols, principles, and procedures developed and discussed in this paper.